Survey of equine veterinarians regarding primary equine back pain in the United States - Marshall-Gibson, Marianne E.; Durham, Matthew G.; Seabaugh, Kathryn A.; Moorman, Valerie J.; Ferris, Dora J. (Frontiers in Veterinary Science, 2023)
Back pain is a common complaint, clinical finding and performance limiting factor in sport horses. This study sought to gather current veterinary trends in the diagnosis, treatment and management of primary equine back pain in the U.S.A.A 22 question survey was distributed electronically to equine practitioners through AAEP and ACVSMR listservs and through closed social media groups. The survey was open from April 20, 2022 to July 5, 2022. Responses were analyzed using Microsoft excel pivot tables.Ninety-seven survey responses were obtained and analyzed. Respondents reported the clinical signs most frequently relayed to them by the owner/rider/trainer of horses diagnosed with primary back pain were behavioral issues and poor performance. Most common diagnostic tests reported were radiography of the spinous processes, thoraco-lumbar vertebral bodies, and transcutaneous ultrasound of the thoraco-lumbar region. Most common pathologies reported were impinging dorsal spinous processes, degenerative sacro-iliac joint disease, and osteoarthritis in lumbar or thoracic articular process joints. In regards to impinging spinous process ("kissing spine") treatments, 72.2% of respondents recommended surgery only after non-surgical treatments failed, and 14.6% of respondents never recommended surgery. The majority (82%) of respondents reported some level of improvement in clinical signs of primary back pain with rehabilitation alone. To date, there has been no consensus or discussion about common abnormalities, diagnostic tests, treatments or management options for primary equine back pain in the U.S. Results of this survey are This is a provisional file, not the final typeset article a starting point showing current trends in diagnosis, treatment and management of primary equine back pain among equine practitioners in the U.S.A showing 82% of practitioners using rehabilitation as a component of treatment.